Student representative council: addressing information needs of students and evaluation of information dissemination channels used by the SRC of the University of Limpopo462415 - Ntsala, M.; Mahlatji, M. R. (My University, 2016)
Students’ representative formations in institutions of higher learning are responsible for governance and administration of students’ academic matters. That is, they lead and represent students on various platforms on or outside university campuses. For the Student Representative Council (SRC) to be truly representative, it has to have information about matters affecting students and also how the university functions. This will enable students to access information on policies, academic rules and any other information that affect them. The term access, in this article, is taken to mean ability to obtain, read, understand and apply the information efficiently and effectively. It is imperative for students to know the role of the SRC, its activities and challenges that affect students. This will allow active participation of students in university activities and SRC administration to enhance students’ wellbeing at the university. This article argues that there are many students who need SRC intervention upon violation of certain academic policies and rules. It is worth noting however, that due to the inaccessibility of SRC, some of such students are left with little or no information to address their challenges. This is in spite of the fact that the SRC is mostly considered to be better positioned to educate and make information accessible to the students. It is for this reason that this article has sought to investigate how the SRC at the University of Limpopo learn about student’s information needs. It is important that students get the right information, at the right time, at the right place, in the right format using the right information dissemination channel. Moreover to evaluate the dissemination channels in use to reach the entire student body. The article concludes by illustrating how the accessibility of such channels can be improved
Published in: Journal of Public Administration and Development Initiatives. volume1, issue 1, 2016
Keywords: Information needs; Dissemination channels; Communication Channels; Student Representative Council; Policies and procedures; Student government -- Communication; Student government -- South Africa